Value Creation and Socioeconomic Inclusion in South African Maker Communities - Armstrong, Chris; Kraemer-Mbula, Erika (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2022)
In socioeconomic environments affected by high and persistent income inequalities and unemployment, there is a need for participative approaches to innovation in support of socioeconomic inclusion. This article explores the features of collective action, in support of socioeconomic inclusion, identified in South African maker communities. Drawing on data from interviews with participants in seven maker communities, the study explores the kinds of value that participants experience through being part of these communities. Value creation is assessed in terms of the five overlapping cycles of value that Wenger et al. (2011) propose are present in successful communities and networks: immediate value, potential value, applied value, realised value, and reframing value. The study finds that all five value cycles are present in the experiences expressed by the South African maker community participants. The value is found to be particularly pronounced in the immediate valueand applied value cycles. In respect of socioeconomic inclusion, the findings point to strong currents of social inclusion in the immediate value cycle, and strong elements of both social and economic inclusion in the applied value, realised value, and reframing value cycles.